A CORPUS-DRIVEN DESIGN OF A TEST FOR ASSESSING THE ESL COLLOCATIONAL COMPETENCE OF UNIVERSITY STUDENTS - Moreno Jaén, María (International Journal of English Studies, 2009)
This paper reports an assessment of the collocational competence of students of English Linguistics at the University of Granada. This was carried out to meet a two-fold purpose. On the one hand, we aimed to establish a solid corpus–driven approach based upon a systematic and reliable framework for the evaluation of collocational competence in ESL. On the other hand, it was our intention to determine whether students’ collocational thresholds were acceptable. Thus, after revising the theoretical construct of the notion of “collocation”, we accomplished the selection of items drawn from data provided by the Bank of English and the British National Corpus, a procedure intended to ensure the scientific quality of the test design propounded. We designed an 80-item test to assess competence in both the receptive and productive collocational aspects of the written skill. Results revealed that students possess a poor collocational competence, the scores concerning the productive items being, as expected, significantly lower than the receptive ones.